Analytical studies on the incorporation of aluminium in the cell walls of the marine diatom Stephanopyxis turris - Machill, Susanne; Koehler, Lydia; Ueberlein, Susanne; Hedrich, Rene; Kunaschk, Marco; Paasch, Silvia; Schulze, Renate; Brunner, Eike (Biometals, 2013)
The eukaryotic diatoms are unicellular algae. They are well known for their filigree microand nanostructured cell walls which mainly consist of amorphous silica aswell as various organic compounds. However, diatoms are also known to incorporate certain amounts of aluminium into their cell walls. Unexpectedly, enhanced Al concentrations in the Southern Yellow Sea were found to be correlated with a diatom spring bloom. Therefore, we have analyzed the influence of strongly enhanced Al concentrations in the culture medium upon the growth behaviour of the diatom Stephanopyxis turris (S. turris). The uptake and incorporation of Al into the cell walls was monitored. It turned out that S. turris survives aluminium concentrations up to 105.5 lM(2.85 mg/l) in the culturemedium. Under the applied conditions, this corresponds to an Al/Si ratio of 1:1. These large amounts of Al had to be offered in the form of bis-tris-chelates in order to prevent uncontrolled precipitation. Under these conditions, the Al/Si ratio in the cell walls could be increased up to about 1:15 as determined by ICP-OES, the highest amount of aluminium found in diatom cell walls yet. Structural characterization of the biosilica by ATRFTIR and solid-state 27Al NMR spectroscopy revealed that an amorphous aluminosilicate phase is formed where the aluminium exists as four- and sixfoldcoordinated species. © Springer Science+Business Media New York 2013.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Aluminium incorporation; Diatom biosilica; FTIR; ICP-OES; Solid-state NMR